Viking Adventure Supplementary Reading Material - Roderick Hunt; Roderick Hunt (Oxford Reading Tree, 2012)
Nov 10, 2020 · This comprehension pack includes two sheets for each book in the Stage 8 Stories set: The Flying Carpet, The Kidnappers, A Day in London, The Rainbow Machine, Victorian Adventure and Viking Adventure. Pupils will be